Examining Student Teachers’ Agency in an AI-Supported Learning Environment : Q Methodology Research - Chaaban, Youmen; Jung, Song-Gyo; Medina, Johanne; Azem, Jinan Y.; Salminen, Joni; Jansen, Bernard J. (Springer, 2025)
Drawing on a socio-cognitive framework, we explored student teachers’ agency along intrapersonal, behavioral and environmental dimensions within the context of a classroom management course. The study investigated the enactment of student agency in an AI-supported learning environment using an innovative AI conversational chatbot whose outputs are based solely on curated course material. Using Q methodology, the analysis of 22 Q sorts revealed three distinct factors: (1) “I got this…just leave me alone” – self-reliant users confident in their abilities but exhibiting limited ethical awareness and reflective practices, (2) “Cipherbot is helpful, but…” – balanced users demonstrating intentional and ethical engagement, and (3) “A blind date with Cipherbot” – uncritical users heavily reliant on Cipherbot with diminished agency and criticality. The results are discussed in light of ongoing deliberations on the complexities of preparing student teachers for ethical and agentive GenAI use.
Keywords: GenAI; Student teachers; Q methodology; Qatar; fi=Markkinointi|en=Marketing|